Originally Posted by
okokjae Find the value of k in terms of X right?
x^3 + 2x^3 - 5x -6 = (x-2)(x+3)(x-k)
= x^3 + 2x^3 - 5x - 6 = (x^2 + x - 6)(x - k)
= x^3 + 2x^3 - 5x - 6 = (x^3 - (k)x^2 + x^2 - (k)x -6x -(k)6
Subtract x^3 from both sides to get
2x^3 -5x - 6 = (k)x^2 + x^2 - (k)x - 6x - (k)6
Add 6x to both sides to get
2x^3 + x - 6 = (k)x^2 + x^2 - (k)x - (k)6
Subtract x^2 from both sides to get
2x^3 + x^2 + x - 6 = (k)x^2 + (k)x - (k)6
Take k out from the right side to get
2x^3 + x^2 + x - 6 = (k)(x^2 + x - 6) <--------- I may have messed up from this part, check your math too.
Look, we have x^2 + x - 6 on both sides so divide
2x^3 + 1 = (k)